Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1152/ajpregu.00220.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic CNS oxytocin signaling preferentially induces fat loss in high-fat diet-fed rats by enhancing satiety responses and increasing lipid utilization

Abstract: -Based largely on a number of short-term administration studies, growing evidence suggests that central oxytocin is important in the regulation of energy balance. The goal of the current work is to determine whether long-term third ventricular (3V) infusion of oxytocin into the central nervous system (CNS) is effective for obesity prevention and/or treatment in rat models. We found that chronic 3V oxytocin infusion between 21 and 26 days by osmotic minipumps both reduced weight gain associated with the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
131
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(153 citation statements)
references
References 110 publications
(217 reference statements)
21
131
0
1
Order By: Relevance
“…In HFDinduced obese male and female mice (body fat mass: 36%), 10 days of oxytocin treatment decreased abdominal and subcutaneous fat up to 15-20% without reducing muscle mass [39]. Similar effects of oxytocin on fat mass are found in other studies using HFD-induced obese mice/rats [25,29,31,32] and genetically obese models such as db/db [131] and ob/ob mice [37]. This suggests that the cause of decreased BW induced by oxytocin treatment depends not only on the decreased food intake, but also on the stimulation of lipolysis.…”
Section: Clinical Implications Of Oxytocinsupporting
confidence: 73%
See 2 more Smart Citations
“…In HFDinduced obese male and female mice (body fat mass: 36%), 10 days of oxytocin treatment decreased abdominal and subcutaneous fat up to 15-20% without reducing muscle mass [39]. Similar effects of oxytocin on fat mass are found in other studies using HFD-induced obese mice/rats [25,29,31,32] and genetically obese models such as db/db [131] and ob/ob mice [37]. This suggests that the cause of decreased BW induced by oxytocin treatment depends not only on the decreased food intake, but also on the stimulation of lipolysis.…”
Section: Clinical Implications Of Oxytocinsupporting
confidence: 73%
“…We found that mice showed increased energy expenditure with decreased respiratory quotient (RQ) during the light phase of the treatment period [23]. The RQ decrease by oxytocin treatment was also confirmed in rats, monkeys, and humans [25,32,34,35,135]. This reduction of BW by oxytocin may also be mediated by the induction of diet-induced thermogenesis [31,47].…”
Section: Clinical Implications Of Oxytocinmentioning
confidence: 64%
See 1 more Smart Citation
“…Preclinical studies indicate that oxytocin induces lipolysis 14,18 and fat oxidation 18,37,86 , which in turn, independent of food intake, lead to reduced body fat and weight 18 . Notably, oxytocin reduces visceral and liver fat 37 , which are metabolically important fat depots that are associated with an increased risk of the metabolic syndrome and cardiovascular disease 87 .…”
Section: Lipid Metabolism and Body Fatmentioning
confidence: 99%
“…Unlike existing pharmacological options, which primarily target food consumption or absorption, oxytocin not only reduces food intake but, in diet induced obese rodent and nonhuman primate models, also promotes energy expenditure, which enables maintenance of weight reduction 14,18,38,86 . How oxytocin increases energy expenditure is not yet clear; however, some preclinical evidence suggests that oxytocin may lead to preferential preservation of lean body mass, a key determinant of energy expenditure, despite weight loss 86 ; activation of brown fat 32-34 ; and/or the conversion of white adipose tissue to beige fat that is capable of thermogenesis 90,95 .…”
Section: Energy Expenditurementioning
confidence: 99%